Paleo‐metagenomics of North American fossil packrat middens: Past biodiversity revealed by ancient DNA. Issue 5 (20th February 2020) - Moore, Grace; Tessler, Michael; Cunningham, Seth W.; Betancourt, Julio; Harbert, Robert
Abstract: Fossil rodent middens are powerful tools in paleoecology. In arid parts of western North America, packrat ( Neotoma spp.) middens preserve plant and animal remains for tens of thousands of years. Midden contents are so well preserved that fragments of endogenous ancient DNA (aDNA) can be extracted and analyzed across millennia. Here, we explore the use of shotgun metagenomics to study the aDNA obtained from packrat middens up to 32, 000 C 14 years old. Eleven Illumina HiSeq 2500 libraries were successfully sequenced, and between 0.11% and 6.7% of reads were classified using Centrifuge against the NCBI "nt" database. Eukaryotic taxa identified belonged primarily to vascular plants with smaller proportions mapping to ascomycete fungi, arthropods, chordates, and nematodes. Plant taxonomic diversity in the middens is shown to change through time and tracks changes in assemblages determined by morphological examination of the plant remains. Amplicon sequencing of ITS2 and rbcL provided minimal data for some middens, but failed at amplifying the highly fragmented DNA present in others. With repeated sampling and deep sequencing, analysis of packrat midden aDNA from well‐preserved midden material can provide highly detailed characterizations of past communities of plants, animals, bacteria, and fungi present as trace DNA fossils. The prospects for gaining more paleoecological insights from aDNA for rodent middens will continue to improve with optimization of laboratory methods, decreasing sequencing costs, and increasing computational power. Abstract : Past biodiversity revealed by ancient DNA metagenomics of North American fossil packrat middens. Here, we test shotgun sequencing of ancient DNA to identify the biological components of Late Pleistocene packrat middens. These methods are the first step in establishing robust paleogenomic methods to the analysis of well‐preserved midden materials.